Penggunaan Limbah Beton Sebagai Bahan Perbaikan Tanah Lempung Terhadap Parameter Kuat Geser - , Solekan; , Ir. Renaningsih, M.T; , Anto Budi Listyawan, S.T., M.Sc (2017)
Soil did shrinkage in dray condition and expanded in wet condition called expansion. When the building construction on the soil that will make damage on the construction, those are like highway, bridge, plate, foudation, consolidation and others, (Bowles, 1986). Based on this research which has been done, improvement of soft clay with concret waste with variation precetage of 5%, 8%, and 10%. The result of fisis test was gotten value of density of 2,607, 14,11% of water content, 65,04% of liquid limit, 15,23 of shrinkage limit and 44,51% of platic index, wherease on the soil with mixture of concrete waste with 5%,8%, and10%, the value of density always increased, value of water content decreased, value of liquid limit decreased, plastic limit increased, shrinkage limit decreased, and plastic index decreased. Clasification of USCS with origin soil and soil mixtured with concrete waste of 5%, 8%, and 10% into CH specification with soil clay of unorganic with high plasticity. On the compaction test, in more percetage of concrete waste used so it will make more value of optimum water content, the highest value is on mixture of concrete waste with 10% is as high as 27,00%, it is like the dry maximum value of vomlume increased too in every addition of concrete waste, its highest value on mixture of waste concrete with 10% is 1,36 (gr/cm3). The result of DST of sheare inside angle tended increasing with percentage of 5%,8%, and10%. The value is in the soil with concrete waste of 10% in second trial with 25,26%. Wherease cohesion value increased too because of apparent cohesion, the smallest value happend on the soil with mixture of nilai 5% on the first trial is 0,825( kg/cm2 ).